2020
DOI: 10.1021/acs.orglett.0c04012
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Iridium-Catalyzed Hydrogenation of Conjugated Trisubstituted Enones

Abstract: Asymmetric hydrogenation of conjugated enones is one of the most efficient and straightforward methods to prepare optically active ketones. In this study, chiral bidentate Ir–N,P complexes were utilized to access these scaffolds for ketones bearing the stereogenic center at both the α- and β-positions. Excellent enantiomeric excesses, of up to 99%, were obtained, accompanied with good to high isolated yields. Challenging dialkyl substituted substrates, which are difficult to hydrogenate with satisfactory chira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Previous work already demonstrated that the hydrogenation of β-prochiral unsaturated carbonyl compounds follows the selectivity model and that it is also enantiodivergent which again is in accordance with the selectivity model (Fig. 4a) 29,30 . However, during the evaluation of the two isomeric forms of the α-disubstituted enone 1a it was found that both (E)-1a and (Z)-1a surprisingly gave rise to the (R)-enantiomer, and in high selectivity (99% and 95% ee respectively, Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Previous work already demonstrated that the hydrogenation of β-prochiral unsaturated carbonyl compounds follows the selectivity model and that it is also enantiodivergent which again is in accordance with the selectivity model (Fig. 4a) 29,30 . However, during the evaluation of the two isomeric forms of the α-disubstituted enone 1a it was found that both (E)-1a and (Z)-1a surprisingly gave rise to the (R)-enantiomer, and in high selectivity (99% and 95% ee respectively, Fig.…”
Section: Resultssupporting
confidence: 86%
“…Most important, experimental support for this hypothetical coordination was reported by an elegant low-temperature NMR study of Pfaltz in which a fundamental intermediate, an Ir III dihydride alkene complex akin to the above-described, was identified 28 . Intriguingly, although the model correctly predicts the stereochemical outcome for most olefins, it cannot be used for the hydrogenation of olefins having a conjugated carbonyl group 29,30 . Whereas the correct absolute configuration can be predicted for the formation of β-disubstituted carbonyl compounds, hydrogenation of α-disubstituted unsaturated carbonyl compounds yield the opposite enantiomer compared to the prediction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analytical data are consistent with the literature. 36 General procedure for the one-pot reaction of α-chiral ketones (GP7)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The analytical data are consistent with the literature. 35 One-Pot Reaction of -Chiral Ketones; General Procedure GP7 Under inert conditions, LiHMDS (1.0 M in THF/ethylbenzene, 0.76 mL, 0.76 mmol, 1.5 equiv) in dimethylformamide (30 mL) was cooled to -40 °C. The enolisable Weinreb amide equivalent (0.50 mmol, 1.0 equiv) was added dropwise, followed by the addition of the electrophile (1.50 mmol, 3.0 equiv).…”
Section: J Fährmann Et Almentioning
confidence: 99%
“…Chiral β,β-disubstituted ketones are key structural subunits of many bioactive natural products and serve as prevalent building blocks in many pharmaceuticals and agrochemicals (Scheme ). Several approaches have been developed in the past few decades, such as asymmetric hydrogenation of β,β-distubstituted enones, enantioselective 1,4-addition of enones, and asymmetric reduction of β,β-disubstituted α,β-unsaturated ketones . Compared to hydrogenation using hydrogen gas, 1,4-reductions of enones with reductive reagents could be more easily carried out in the laboratory due to the safety issue.…”
mentioning
confidence: 99%